A Robust, Freestanding MXene‐Sulfur Conductive Paper for Long‐Lifetime Li–S Batteries. (27th May 2019) - Tang, Huan; Li, Wenlong; Pan, Limei; Tu, Kejun; Du, Fei; Qiu, Tai; Yang, Jian; Cullen, Conor P.; McEvoy, Niall; Zhang, Chuanfang (John)
Abstract: Freestanding, robust electrodes with high capacity and long lifetime are of critical importance to the development of advanced lithium–sulfur (Li–S) batteries for next‐generation electronics, whose potential applications are greatly limited by the lithium polysulfide (LiPS) shuttle effect. Solutions to this issue have mostly focused on the design of cathode hosts with a polar, sulfurphilic, conductive network, or the introduction of an extra layer to suppress LiPS shuttling, which either results in complex fabrication procedures or compromises the mechanical flexibility of the device. A robust Ti3 C2 T x /S conductive paper combining the excellent conductivity, mechanical strength, and unique chemisorption of LiPSs from MXene nanosheets is reported. Importantly, repeated cycling initiates the in situ formation of a thick sulfate complex layer on the MXene surface, which acts as a protective membrane, effectively suppressing the shuttling of LiPSs and improving the utilization of sulfur. Consequently, the Ti3 C2 T x /S paper exhibits a high capacity and an ultralow capacity decay rate of 0.014% after 1500 cycles, the lowest value reported for Li–S batteries to date. A robust prototype pouch cell and full cell of Ti3 C2 T x /S paper // lithium foil and prelithiated germanium are also demonstrated. The preliminary results show that Ti3 C2 T x /S paper holds great promise for future flexible and wearable electronics. Abstract : A robust, freestanding Ti3 C2 T x /sulfur conductive paper for Li–S battery cathodes is prepared. The unique interactions between polysulfides and Ti3 C2 T x lead to the continuous, in situ growth of sulfate complex layer, which effectively suppresses the polysulfide shuttling. Consequently, a high capacity of 1383 mAh g −1, good rate handling, and ultra‐low capacity fade rate of 0.014% after 1500 cycles are obtained. Furthermore, Ti3 C2 T x /S‐based pouch cells and full cells with promising preliminary results are also demonstrated.